Regulation of ER stress-induced apoptotic and inflammatory responses via YAP/TAZ-mediated control of the TRAIL-R2/DR5 signaling pathway - Y. El Yousfi; F. J. Fernández-Farrán; F. J. Oliver; A. López-Rivas; R. Yerbes (Cell Death Discovery)
Abstract In tumors, cancer cells are frequently exposed to adverse environmental conditions that result in endoplasmic reticulum (ER) stress. Mechanical signals emerging from extracellular matrix (ECM) rigidity and cell shape regulate the activity of transcriptional co-activators Yes-associated protein (YAP) and its paralog Transcriptional Coactivator with PDZ-binding motif (TAZ). However, the role of ECM rigidity and YAP/TAZ in tumor cell fate decisions under ER stress remains relatively unexplored. Our results suggest that the YAP/TAZ system plays an important role in the control of ER stress-induced cell death by mechanical signaling arising from ECM stiffness in tumor cells. Mechanistically, YAP/TAZ regulates apoptosis induced by ER stress in tumor cells by controlling the activation of the TRAIL-R2/DR5-mediated extrinsic apoptotic pathway through a dual mechanism. On the one hand, the YAP/TAZ system prevents intracellular TRAIL-R2/DR5 clustering in tumor cells. On the other hand, it inhibits cFLIP down-regulation in tumor cells experiencing ER stress. In addition, YAP/TAZ controls the expression of pro-inflammatory interleukin-8 (IL-8/CXCL8) in tumor cells undergoing ER stress by a TRAIL-R2/DR5/caspase-8-dependent mechanism. Although other mechanisms may also be involved in controlling cell death and inflammation in tumor cells facing environmental stress, our results support a model in which regulation of the subcellular localization and activity of the YAP/TAZ transcriptional co-activators could contribute to the microenvironmental control of cell fate decisions in tumor cells undergoing ER stress.